The Suitability of Indole as an Index of Spoilage of Prawns - Thomas, Francis; T.S.G., Iyer; P.R.G., Varma (Fishery Technology, 2025)
The indole content in prawn meat from pre-processing centres around Cochin was in the range 0.5 to 3.1 ng 100g !. 43 percent of the sample contained only 1 ng lOOg-’ or less. On the other hand, the indole content in commercially frozen prawn samples collected from the local processing factories was between 0 to 20.6 ng lOOg1. Only 28 percent of such samples contained 1 ng lOOg’1 or less of indole. This indicates an increase in indole content during processing operations prior to freezing. The indole content in the spoiled prawn meat discarded by the suppliers themselves after final checking was in the range 0.5 to 15.6 Hg lOOg1. The formation of indole in prawns during storage at ambient temperature and ice was also studied. During storage of Heterocarpus woodmasoni, Penaeus indicus, P. monodon and Metapemeus monoceros at ambient temperature, indole content above 25 (ig lOOg"1 was reached only after a period of 12 to 18 h. During storage of P. indicus for 22 days in ice the indole content increased from 0.5 to 5.0 (ig lOOg ’.